Two axiomatic approaches to the probabilistic serial mechanism. Issue 1 (January 2014) - Hashimoto, Tadashi; Hirata, Daisuke; Kesten, Onur; Kurino, Morimitsu; Ünver, M. Utku
<x xml:space="preserve">Abstract</x> This paper studies the problem of assigning a set of indivisible objects to a set of agents when monetary transfers are not allowed and agents reveal only ordinal preferences, but random assignments are possible. We offer two characterizations of the probabilistic serial mechanism, which assigns lotteries over objects. We show that it is the only mechanism that satisfies non‐wastefulness and ordinal fairness, and the only mechanism that satisfies sd‐efficiency, sd‐envy‐freeness, and weak invariance or weak truncation robustness (where "sd" stands for first‐order stochastic dominance).